White Matter Microstructure is Associated with Auditory and Tactile Processing in Children with and without Sensory Processing Disorder - Chang, Yi-Shin; Gratiot, Mathilde; Owen, Julia P.; Brandes-Aitken, Anne; Desai, Shivani S.; Hill, Susanna S.; Arnett, Anne B.; Harris, Julia; Marco, Elysa J.; Mukherjee, Pratik (Frontiers in Neuroanatomy, 2016)
Sensory processing disorders (SPD) affect up to 16% of school-aged children, and contribute to cognitive and behavioral deficits impacting affected individuals and their families. While sensory processing differences are now widely recognized in children with autism, children with sensory-based dysfunction who do not meet autism criteria based on social communication deficits remain virtually unstudied. In a previous pilot diffusion tensor imaging (DTI) study, we demonstrated that boys with SPD have altered white matter microstructure primarily affecting the posterior cerebral tracts, which subserve sensory processing and integration. This disrupted microstructural integrity, measured as reduced white matter fractional anisotropy (FA), correlated with parent report measures of atypical sensory behavior. In this present study, we investigate white matter microstructure as it relates to tactile and auditory function in depth with a larger, mixed-gender cohort of children 8 to 12 years of age. We continue to find robust alterations of posterior white matter microstructure in children with SPD relative to typically developing children, along with more spatially distributed alterations. We find strong correlations of FA with both parent report and direct measures of tactile and auditory processing across children, with the direct assessment measures of tactile and auditory processing showing a stronger and more continuous mapping to the underlying white matter integrity than the corresponding parent report measures. Based on these findings of microstructure as a neural correlate of sensory processing ability, diffusion MRI merits further investigation as a tool to find biomarkers for diagnosis, prognosis and treatment response in children with SPD. To our knowledge, this work is the first to demonstrate associations of directly measured tactile and non-linguistic auditory function with white matter microstructural integrity – not just in children with SPD, but also in typically developing children.